Hyperchaos for improving the security of medical data - N. Lagmiri, S; Elalami, J; Sbiti, N; Amghar, M (International Journal of Engineering and Technology, 2018)
Because of the widespread use of medical images and signals in hospitals and healthcare communities, information security and medical data encryption are becoming more important. Cryptography has a specific role, is to protect data against unauthorized access. In this paper, we propose an efficient encryption scheme for medical data using a new hyperchaotic system applied with two algorithms: the first based on random key generation from initial conditions to encrypt a brain MRI and the second algorithm using chaotic masking technique to encrypt the heartbeat signal. The scheme achieves secure encryption and his robustness is measured by various metrics such as histogram analysis, key sensitivity, correlation coefficient and PSNR test. We conclude from the experimental results that the scheme promises stronger resistance against diverse forms of common attacks and high sensitivity to the security keys.Â Â